Morphological Characterisation of Three Populations of Heterobranchus longifilis from Nigeria - Alih Raphael A,; Solomon Shola Gabriel,; Olufeagba Samuel Olabode,; Cheikyula Joseph O.,; Abol-Munafi Ambok Bolong,; Mhd Ikhwanuddin ,; Okomoda Victor Tosin, (Tropical Life Sciences Research, 2024)
This study attempted to discriminate the population of Heterobranchus longifilis in Nigeria using their morphological characteristics. Therefore, 60 sexually mature wild samples of H. longifilis (1:1 for the male and female ratio) of relatively similar size (40 cm) were collected from three eco-regions namely, Guinea Savanna (Benue River, Makurdi), Rainforest Savanna (Niger River, Onitsha) and Sahel Savanna (Rima River, Sokoto). They were transported to the hatchery unit of the Fisheries and Aquaculture Department, Joseph Sarwan Tarka University Makurdi where the morphometric data was collected. The data for 39 traditional morphometric measurements and 5 meristic counts obtained from each fish were subjected to univariate and multivariate analysis. While significant differences were observed in some parameters following univariate analysis; it was revealed that the morphometric parameters and meristic counts could not separate the fish from the different ecoregions into distinct multivariate spaces or clusters following Principal Component Analysis. Hence, this suggests that morphological parameters cannot be used to discriminate H. longifilis from the different ecoregions. Studies using molecular markers are needed to further characterise the distinctiveness of the different populations.